The Investigation of Lyric Poems of Qasim Anwar's influence from Shams Lyric Poems with Intertextuality Approach - Mahnoosh Jorak; Habibollah Abbasi (Matn/Pizhūhī-i Adabī, 2023)
The flow of mystical poetry flourished after the emergence of prominent poets, especially Rumi, and also after the Mongol invasion. One of the famous poets is Qasim Anwar, who was famous during his lifetime. The multiplicity of manuscripts available from his divan confirms this to some extent. In this article, we examined the effectiveness of the poet's lyric poems from Shams Molavi's lyric poems at three linguistic, rhetorical, and musical levels with descriptive and analytical methods and an intertextual approach. And we concluded that the poetry of Qasim Anwar, under the influence of the literary tradition before him, is often devoid of poetic passion and resembles poetic scientific interpretation of mystical issues with the specific linguistic dictionary of Sufis, revolves more around imitation and repetition and is devoid of creativity and initiative and his words and those of his contemporaries follow tradition.